The Effect of the Buzz Group Method on Student Learning Activity in Social Studies Subjects at Elementary School - Fatmawati, Dewi; Rezania, Vanda (research, training and philanthropy institution Natural Aceh, 2024)
The buzz group method is one of the methods used in learning to solve problems. The material in social science subjects is learning that contains topics about social science in society, so learning activeness is needed to solve problems. This study aims to determine the effect of the buzz group method on learning activeness in grade V social studies subjects at SDN Kebakalan Porong. This study used a quantitative approach with a Pre-Experimental research type with One one-group pretest-posttest type. The population used was 32 people. Data collection techniques in the research were conducted using questionnaire sheets and documentation. Data analysis techniques used by researchers include normality tests and T-tests using Paired Sample T-tests. Based on the results of the research data obtained, the average value of learning activeness in the pretest was 67%, while the average value of learning activeness in the posttest showed an increase of 80%. This research proves that the buzz group method affects student learning activeness in 5th-grade social studies subjects at SDN Kebakalan Porong.